Analisis Fasilitas yang Memberikan Nilai Tambah pada Terminal Keberangkatan terhadap Tingkat Kepuasan Penumpang di Bandar Udara Internasional Sultan Hassanudin Makassar - Ariesti, Yudith Delta Cerria; Amir, Elfi; Purwaningtyas, Dian Anggraini (Jurnal Ground Handling, 2025)
This study analyzes the impact of value-added facilities at the departure terminal on passenger satisfaction at Sultan Hasanuddin International Airport Makassar. The main objective is to measure how much influence these facilities have. Using a quantitative analysis, this study involved 100 passenger respondents. Data were collected through a validated and reliability-tested questionnaire. The t-test results showed a significance value of 0.01 (<0.05), indicating that value-added facilities have a significant impact on passenger satisfaction. The coefficient of determination (R-squared) of 0.503 indicates that 50.3% of passenger satisfaction at Sultan Hasanuddin International Airport Makassar is influenced by value-added facilities at the departure terminal, while 49.7% is influenced by other variables outside the study. The conclusion of this study is that value-added facilities have a positive and significant impact on passenger satisfaction at Sultan Hasanuddin International Airport Makassar.